2001
DOI: 10.1046/j.1365-2672.2001.01334.x
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics and antagonistic potential of enterococci colonizing the phyllosphere of grasses

Abstract: Aims: To investigate the spatial and temporal dynamics of enterococci colonizing forage grass and their ability to produce bacteriocins. Methods and Results: Enterococci could be detected on above-ground plant parts throughout the growing season, with high continuity but low cell numbers (2á60´10 1 ± 6á16´10 4 cfu g ±1 fresh matter). A total of 750 strains were isolated and identi®ed by their whole-cell protein patterns as Enterococcus faecalis (7á9%), Ent. mundtii (7á9%), Ent. casseli¯avus (5á5%), Ent. faeciu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 42 publications
3
37
0
Order By: Relevance
“…E. faecalis is the most common specie isolated from clinical samples (80-90%), interacts with many other organisms and has effects on the environment. In the other hand, E. casseliflavus has been reported in 20% of beach samples and it is associated with natural source, such as plants [31][32][33]. This is consistent with the results found in this research.…”
Section: Resultssupporting
confidence: 92%
“…E. faecalis is the most common specie isolated from clinical samples (80-90%), interacts with many other organisms and has effects on the environment. In the other hand, E. casseliflavus has been reported in 20% of beach samples and it is associated with natural source, such as plants [31][32][33]. This is consistent with the results found in this research.…”
Section: Resultssupporting
confidence: 92%
“…Furthermore, the finding that certain strains of Enterococcus spp. may have environmental adaptations, for instance, E. casseliflavus in submerged aquatic vegetation (15) and E. casseliflavus, E. faecalis, E. faecium, E. hirae, E. mundtii, E. sulfureus, and many other strains resembling E. faecalis from forage crops (50,235,261), strongly supports the existence of plant-associated enterococci.…”
Section: Environmental Reservoirs and Extraenteric Habitatsmentioning
confidence: 86%
“…Recent studies have expanded these findings to forage and crop species (235,261). Mundt (237) initially suggested that the occurrence of enterococci in plants was seasonal, with maximum recovery in late summer (September), and that these bacteria were transient populations most likely introduced by insects and wind (237).…”
Section: Environmental Reservoirs and Extraenteric Habitatsmentioning
confidence: 99%
See 1 more Smart Citation
“…Natural bacterial populations have been found to consist of a wide variety of genotypes that differ in their ability to both suppress and withstand conspecifics (Ott et al, 2001;Riley et al, 2003;Davelos et al, 2004;Vos and Velicer, 2009). A trade-off between an advantage in growth (resource or scramble competition) and an advantage in 'killing capacity' or 'resistance capacity' (interference competition) lies at the basis of theoretical models attempting to explain the coexistence of strains differing in antibiotic production and sensitivity (Hsu and Waltman, 1997;Czaran and Hoekstra, 2003;Gardner and West, 2004;Czaran and Hoekstra, 2007;Brown et al, 2009;Hibbing et al, 2010).…”
Section: Discussionmentioning
confidence: 99%